Comparative activities of ampicillin and teicoplanin against Enterococcus faecalis isolates - Georgios V. Zacharopoulos; Georgios A. Manios; Marios Papadakis; Dimitra Koumaki; Sofia Maraki; Dimitrios Kassotakis; Eelco De Bree; Andreas Manios (BMC Microbiology, 2023)
Abstract Background Enterococcus faecalis remains one of the most common pathogens causing infection in surgical patients. Our goal was to evaluate the antibiotic resistance of E. faecalis, causing infections in a surgical clinic, against two antibacterial drugs, ampicillin and teicoplanin. One commonly administered in the past for such infections, ampicillin, and another newer, teicoplanin, which demonstrated exceptionally good efficacy. Methods Data from 1882 isolates were retrieved from the microbiology department database during two 5-year periods. Standard biochemical methods were employed for the identification of the isolates. The prevalence of E. faecalis among patients with clinical evidence of infection in a surgical oncology ward was assessed. Confidence interval (CI) as well as standard error (SE) were calculated. Moreover, the annual incidence of E. faecalis infections in this surgical ward was recorded. The susceptibility of E. faecalis to ampicillin and teicoplanin was studied and compared using Fisher’s exact test. Results and conclusion Results showed that the incidence of E. faecalis infections in the surgical clinic was increasing. Ampicillin, in the later year period, was not statistically different from teicoplanin in treating E. faecalis infections. Consequently, ampicillin seems currently to be an effective antibiotic against such infections that could be used as empiric therapy.